Health-related quality of life among Chinese patients with Crohn’s disease: a cross-sectional survey using the EQ-5D-5L - Ziyun Gao; Pei Wang; Jie Hong; Yuqing Yan; Tianying Tong; Bin Wu; Jun Hu; Zhenhua Wang (Health and Quality of Life Outcomes, 2022)
Abstract Background Crohn’s disease (CD) is a chronic disease that may have an adverse impact on health-related quality of life (HRQoL). This study aimed to describe the HRQoL of CD patients and assess correlating factors using the EQ-5D-5L in China. Methods We recruited CD patients at Shanghai Renji Hospital from October 2018 to May 2019. The data collected included demographic and clinical information, medical expenditures, and EQ-5D-5L questionnaire responses. The chi-square test or Fisher’s exact test was applied to analyse the proportion of patients in subgroups at each level. After the selection of correlating variables by univariate analysis, multivariate regression analyses were used to explore the correlating factors of HRQoL in CD patients. Results A total of 202 CD inpatients with a mean disease duration of 3.3 years were enrolled in the study. A total of 71.8% of patients were males, and 49.5% of patients were aged between 30 and 49 years. The average EQ-5D-5L utility score was 0.85, with a standard deviation (SD) of 0.12. Males, ileum lesions, remission status, and lower expenditure predicted higher EQ-5D-5L scores. In each EQ-5D-5L dimension, the proportion of patients differed significantly by gender, disease activity and location subgroup. In the multivariate regression models, being in an active CD state and using antibiotics had significantly adverse impacts on HRQoL (p < 0.05). Conclusions CD may have a significant negative impact on HRQoL in Chinese CD patients. Being in an active phase of the disease and using antibiotics were identified as affecting HRQoL.